Advances in oilwell cement retarders: a bibliometric and systematic review of mechanisms, challenges, emerging trends, and future directions - Nwaichi, Peter Ikechukwu; Norida, Ridzuan; Nwaichi, Eucharia Oluchi; Umunnawuike, Chika; Abutu, David; Nyah, Francis; Money, Barima; Agi, Augustine Aja (Springer Nature, 2025)
Cement retarders play a critical role in oilwell cementing by controlling slurry setting and thickening times, ensuring proper placement and enhanced zonal isolation under diverse downhole conditions. However, at elevated temperatures, challenges such as thickening time reversal, premature setting, and abnormal gelation can compromise cement performance. Therefore, the objective of this research is to present a comprehensive understanding of retarder mechanisms and their interactions with cementitious material for deep and high-temperature oilwells. This study employs a bibliometric and systematic literature review, analyzing 559 articles from the Scopus database published between 2000 and February 2025 to assess the current knowledge on cement retarders. Key technical mechanisms, including adsorption, dissolution, complexation, precipitation, and nucleation inhibition, are examined alongside practical challenges and performance optimization strategies. The review further identifies emerging materials such as sugar derivatives that show promise for improving thermal stability, mechanical properties, and environmental compatibility of cement slurries. Scientific mapping also highlights influential authors, institutions, journals, and keyword trends. Analysis shows that the increase in research activity between 2016 and 2024 is driven by the need to improve wellbore stability and reduce environmental impact. Future research directions emphasize the development of eco-friendly retarders, advanced admixtures, and smart systems for real-time rheological control. This study provides a consolidated technical and bibliometric foundation to guide innovations in oilwell cementing for enhanced operational efficiency and sustainability.